(untitled) (World Economics and Finance Bulletin, 2022)
The basic concepts and principles of management, modern approaches to the management of a service organization, as well as their specific features in the field of socio-cultural service and tourism are considered. Attention is paid to the adoption of managerial decisions and the information systems supporting them